Book distribution in digital age (on the examples of bookselling enterprises of Siberia and the Far East - O. N. Alshevskaja (Библиосфера)
This article summarizes the experience of the book distribution companies on the use of digital technology: «Print-On-Demand», Internet-shops, electronic client databases, etc. As one of the elements of success in book-selling business in the digital age – the development of cultural and leisure activities in traditional book store.